2017
DOI: 10.1002/lary.26686
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric cochlear implantation: Variation in income, race, payer, and charges across five states

Abstract: 4. Laryngoscope, 128:954-958, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
0
15
1
Order By: Relevance
“…Unlike what has been described in other otolaryngologic procedures, such as cochlear implantation, insurance status did not significantly impact overall decannulation or time to decannulation in dsLTR 11,28,29 . A possible explanation for this, is that the majority (92.7%) of our cohort had a tracheostomy in place prior to dsLTR.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Unlike what has been described in other otolaryngologic procedures, such as cochlear implantation, insurance status did not significantly impact overall decannulation or time to decannulation in dsLTR 11,28,29 . A possible explanation for this, is that the majority (92.7%) of our cohort had a tracheostomy in place prior to dsLTR.…”
Section: Discussioncontrasting
confidence: 52%
“…Unlike what has been described in other otolaryngologic procedures, such as cochlear implantation, insurance status did not significantly impact overall decannulation or time to decannulation in dsLTR. 11,28,29 A possible explanation for this, is that the majority (92.7%) of our cohort had a tracheostomy in place prior to dsLTR. As pediatric tracheostomy is associated with high medical utilization, accounting for 1.4 billion U.S. dollars in hospitalizations in 2009, we may see less of and impact of insurance status after dsLTR.…”
Section: Discussionmentioning
confidence: 94%
“…Concerning geography's effect on age at CI, two studies found no difference in the average age at CI between states. 24,37 However, Bush et al 2013 25 found a direct relationship of age at CI with distance to CI center in Kentucky.…”
Section: Usa: Sociological Factorsmentioning
confidence: 99%
“…Disparities in healthcare delivery in pediatric otolaryngology have been well-documented, arising from multiple factors including race, socioeconomic status, insurance status, and access to care. 1 This has been demonstrated in children with a variety of otolaryngologic conditions, such as hearing loss, 2,3 rhinosinusitis, 4,5 sleep-disordered breathing, 6,7 and otitis media. [7][8][9] Lack of timely care can lead to differences in outcomes and development.…”
Section: Introductionmentioning
confidence: 99%